Beyond the Neuron: The Integrated Role of Glia in Psychiatric Disorders - André Demambre Bacchi (Neuroglia)
In recent decades, substantial evidence has highlighted the integral roles of neuroglia, particularly astrocytes, microglia, oligodendrocytes, and ependymal cells, in the regulation of synaptic transmission, metabolic support, and immune mechanisms within the central nervous system. In addition to their structural role, these cells actively modulate neurotransmitter homeostasis and influence neuronal plasticity, thereby affecting cognition, mood, and behavior. This review discusses how neuroglial alterations contribute to the pathophysiology of five common psychiatric disorders: major depression, bipolar disorder, anxiety disorders, attention-deficit/hyperactivity disorder (ADHD), and schizophrenia. We synthesized preclinical and clinical findings illustrating that glial dysfunction, including impaired myelination and aberrant neuroinflammatory responses, often parallels disease onset and severity. Moreover, we outline how disruptions in astrocytic glutamate uptake, microglia-mediated synaptic pruning, and blood–brain barrier integrity may underlie the neurobiological heterogeneity observed in these disorders. The therapeutic implications range from anti-inflammatory agents to investigational compounds that aim to stabilize glial function or promote remyelination. However, challenges due to interindividual variability, insufficient biomarkers, and the multifactorial nature of psychiatric illnesses remain. Advances in neuroimaging, liquid biopsy, and more precise molecular techniques may facilitate targeted interventions by stratifying patient subgroups with distinct glial phenotypes. Continued research is essential to translate these insights into clinically efficacious and safe treatments.